2001
DOI: 10.1210/jcem.86.6.7549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Selective Estrogen Receptor Modulator, Raloxifene, on the Somatotropic Axis and Insulin-Glucose Homeostasis

Abstract: Raloxifene is the first selective estrogen receptor modulator registered for the prevention and treatment of postmenopausal osteoporosis. In addition to direct effects on bone cells, estrogen and raloxifene may act indirectly via changes in hormonal homeostasis. However, the menopause-related decrease in serum insulin-like growth factor I (IGF-I) and the increase in insulin or glucose are not always reversed by estrogen replacement. Especially orally administered estrogen was reported to decrease serum IGF-I l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The decrease in insulin sensitivity seen in the raloxifene group was not associated with an increase in BMI, central fat mass, or percentage body fat. This is consistent with other longer‐duration studies that have shown no change in BMI with raloxifene 28 . This suggests that the decrease in insulin sensitivity with raloxifene seen in this study may involve other mechanisms besides changes in body composition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The decrease in insulin sensitivity seen in the raloxifene group was not associated with an increase in BMI, central fat mass, or percentage body fat. This is consistent with other longer‐duration studies that have shown no change in BMI with raloxifene 28 . This suggests that the decrease in insulin sensitivity with raloxifene seen in this study may involve other mechanisms besides changes in body composition.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with other longer-duration studies that have shown no change in BMI with raloxifene. 28 This suggests that the decrease in insulin sensitivity with raloxifene seen in this study may involve other mechanisms besides changes in body composition.…”
Section: Discussionmentioning
confidence: 67%
“…Raloxifene is a selective estrogen receptor modulator indicated for the treatment and prevention of osteoporosis in postmeno− pausal women [1], and has been shown to exert some beneficial effects on serum lipids, fibrinogen, and markers of inflammation [2 ± 4]. The effects of raloxifene treatment on glucose and insulin metabolism are controversial; one study has reported unchang− ed insulin sensitivity compared to baseline [5] although both de− creased [6,7] and increased insulin sensitivity [8,9] have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Osteoporosis is a systemic skeletal disease characterized by low bone mass and microarchitectural deterioration of bone tissue, with a consequent decrease in bone mineral density (BMD) and increase in bone fragility and susceptibility to fracture. [4][5][6][7] Aim of the present study to assess the effect of raloxifene in reducing the risk of postmenopausal fracture amongst osteoporotic subjects. Hence; we planned the present study to assess and compare two different management protocols for treating patients with multiple knee ligament injuries.…”
Section: Introduction_____________________mentioning
confidence: 99%